Genetic association study for RSV bronchiolitis in infancy at the 5q31 cytokine cluster. - Forton, J; Rowlands, K; Rockett, K; Hanchard, N; Herbert, M; Kwiatkowski, D; Hull, J (2009)
BACKGROUND: The pathophysiological basis of severe respiratory syncytial virus (RSV) bronchiolitis in infancy is poorly understood and has hindered vaccine development. Studies implicate the cell-mediated immune response in the pathogenesis of the disease. A recent twin study estimated a heritable contribution of 22% to RSV bronchiolitis. Genetic epidemiology provides a new approach to identifying important immune determinants of disease severity. METHODS: A comprehensive high-density gene-region association study for severe RSV bronchiolitis in infancy at 5q31 across 11 genes including the Th2-cytokine cluster was performed. A haplotype tagging approach was used to analyse genetic variation at 113 single nucleotide polymorphisms (SNPs) in 780 independent cases and 1045 controls. The study had sufficient power to detect small effects, perform extensive haplotype analysis and analyse both a principal phenotype and a refined age-limited phenotype enriched for first-exposure RSV infection. RESULTS: SNP associations were found at IL4 and a highly significant risk haplotype was identified across IL13 CNS-1 and IL4 (odds ratio 1.69, p<0.0001), present in both case-control and family-based analyses. All associations were strongest for a phenotype limited to <6 months of age, implicating this locus in primary RSV disease. The same risk haplotype has previously been shown to be associated with increased IL13 expression. CONCLUSIONS: A haplotype at IL13-1L4, which is associated with increased IL13 production, confers an increased risk of severe primary RSV bronchiolitis in early infancy. This study, together with previous studies implicating the same locus in atopic sensitisation, suggests that primary RSV bronchiolitis and atopy share a genetic contribution at the IL13-IL4 locus.